Qualidade agronômica do lodo de esgoto cultivado com Urochloa brizantha cv. marandu na presença de acelerador de compostagem, superfosfato simples e Kcl - Jonas Pereira Pontes (2022)
Sewage sludge is a waste from sewage treatment plants with enormous potential for use as an organic fertilizer. However, it needs a stabilization process, in order to eliminate the odor and attract disease vectors and harmful organisms. Given the above, the objective of this work was to evaluate the sewage sludge cultivated with Urochloa brizantha cv. Marandu in the presence and absence of composting accelerator (CA), simple superphosphate (SS) and KCl, for later use as an organic fertilizer. The experiment was carried out in a randomized block design, with four replications, distributed in a 2³ factorial scheme, corresponding to the presence and absence of composting accelerator (0 and 30.7 L t-1), two doses of simple superphosphate (SS) (0 and 6 kg t-1 of P2O5) and two doses of KCl (0 and 3.6 kg t-1 of K2O). Lineage bags of 30 liters were used for the packaging of sewage sludge, establishing a layer of 30 cm in height and sown with 100 seeds of U. brizhanta per m2, maintaining after thinning 18 plants per m2, with 90-day growing period. In the analysis of shoot dry matter (PA), root (RZ), total dry matter (MT) and PA/RZ ratio, the best results were those that had applied P2O5 and K2O. Assessing the levels of organic C and N, both met the requirements of the legislation for the purpose of registering the product as an organic fertilizer. Observing the values of C/N and pH-H2O, as a function of CA applications and doses of SS and KCl, the C/N ratio increased with the application of phosphate fertilizer. The pH of sewage sludge increased with the application of potassium fertilizer. Both CTC and CTC/C ratio were not influenced by the treatments. From the above, it was found that fertilization with SS or KCl favored the production of grass biomass and that CA was practically ineffective on this variable and also on the attributes of sewage sludge. In any case, the sewage sludge cultivated with the grass presented agronomic attributes within the limits required for registration as a fertilizer by specific legislation, presenting itself as a quality organic fertilizer for use in plant cultivation.